Test-Retest Reliability of the Speech-Evoked Auditory Brainstem Response in Young Adults - Song, Judy H. (2010)
OBJECTIVE: The speech-evoked auditory brainstem response (ABR) provides an objective measure of subcortical encoding of complex acoustic features. However, the intrasubject reliability of this response in both optimal and challenging listening conditions has not yet been systematically documented. This study aimed to evaluate test-retest reliability of the speech-evoked ABR in young adults. METHODS: In each of two sessions, ABRs were obtained with: 1) a 170 ms/da/ syllable presented in quiet as well as 2-talker and 6-talker babble background noise conditions and 2) a 40 ms/da/ syllable presented in quiet. Test-retest reliability of the responses was analyzed in the frequency and time domains. RESULTS: The speech-evoked ABR does not vary significantly across sessions within individuals on measures of temporal encoding (i.e., peak latencies, stimulus-to-response and response-to-response measures), frequency representation and response magnitude. CONCLUSIONS: The subcortical auditory pathway produces a response to a complex sound that is stable and replicable from session to session. SIGNIFICANCE: By demonstrating the high degree of replicability in optimal and challenging listening conditions, the applicability of the speech-evoked ABR may be increased to examining a range of auditory processing abilities in clinical and research settings.